Note—A Note on Spacecraft for Multi-Floor Layout Planning - Jacobs, F. Robert (Management Science, 1984)
This note provides a brief comparison between a three-dimensional layout planning system recently described in Management Science (Johnson [Johnson, Roger V. 1982. SPACECRAFT for multi-floor layout planning. Management Sci. 28 (4, April) 407–417.]) and a similar system developed earlier (Cinar [Cinar, Unver. 1975. Facilities planning: a systems analysis and space allocation approach. Charles M. Eastman, ed. Spatial Synthesis in Computer-Aided Building Design. Wiley, New York, 19–40.]).